A review on participatory ergonomic approaches: What ‘participants’ mean to the organization? - Selamat, Mohd Nasir; Mohd, Rusyda Helma; Abdul Aziz, Siti Fardaniah; Omar, Nik Hairi; Mukapit, Mukhiffun (Human Resource Management Academic Research Society, 2021)
The involvement of various parties in making work decisions in the organization can have a positive impact. Participation in implementing ergonomics aspect among management and individual level will enable workers to serve to the conformity of the job rather than in adjusting to the environment. Hence, it will avoid emerging problems especially to the workers such low self-effacing, work pressure and job dissatisfaction, low level of health status, which eventually affects workers and organizational performance. The important of understanding the multidimensional, dynamic characteristics of participations and the potential positive and negative impact on the ergonomic work system and workers is emerging. Thus, the main agenda of article is to explore conceptually the roles of numerous participants’ ergonomics approaches included examining the potential negative impact of participation. This paper systematically assesses methodologic aspects of literature reviews which references are made on related studies since 1986 to 2021. The present empirical studies and published in high-impact, peer-reviewed academic journal that indicate the significant of participatory ergonomics in the organisations has been analysis. It is also covers several studies from local and abroad context. Electronic bibliographic databases, conference proceedings, and reference registers were systematically searched to obtain relevant documents. The review described important trends in the literature, including increased attention to be given in implementing participatory ergonomics in the organisations. The review analysis were reported that focus of participants among workers improved task contents, increase quality of working life, enhance workers health, and produce accurate ergonomic workstation as well as increase productivity. Conversely, raise cost of operation, added workforce supply as well as increase workload and work pressure was contributed as adverse impact of participants. Most studies were also mentioned that the implementation of participatory ergonomics contribute to both workers and organizational in term of wellbeing and wellness. Finally, the rules as ‘participant’s approaches in organization are essential for employees and the organization to achieve foster quality performance. Further empirical study is required on the implementation of participatory ergonomic as one of an initiative to improve workers capabilities and organisation competencies.